Penerapan Metode Small Group Discussion Materi Haji Dan Umroh Dalam Meningkatkan Hasil Belajar Siswa Di MTS Perguruan Islam Campalagian Kabupaten Polewali Mandar - Nurfadilah Suaib; Firman Firman; Ahdar Ahdar; Usman Usman; Muzakkir Muzakkir (Journal on Education, 2024)
This thesis discusses the application of the Small Group Discussion Method for Hajj and Umrah in improving student learning outcomes at MTs Campalagian Islamic College, Polewali Mandar Regency. This research aims to find out whether the application of Small Group Discussion can improve student learning outcomes in Islamic Religious Education subjects. Researchers prepare action plans/solutions for problem solving; implementation, namely the researcher carries out the actions that have been formulated in the RPP; observation, namely researchers observing student behavior in participating in learning activities; reflection, namely the researcher records the results of observations and evaluates the results of the observations. The main problem solving process in this research is to improve the learning process by using Small Group Discussions. The results of this research are: (1) The implementation of Small Group Discussion according to the results of observations increases in each cycle, the graph of the increase shows a very good category assessment; (2) Student learning outcomes through the implementation of Small Group Discussions increased from a completion percentage of 26.32% to a completion percentage of 89.47%; (3) the application of the Small Group Discussion method can improve student learning outcomes in the Islamic Religious Education subjects Hajj and Umrah.